Impact of tobacco cultivation on soil and human health in the agricultural ecosystem at Tangail region of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2023)
The study was conducted to determine the impact of tobacco cultivation on soil and human health in the agricultural ecosystem at Bhuapur and Kalihati upazila of Tangail region from January to December 2019. Among them, 40 soil samples were collected, each 20 from Kalihati and Bhuapur Upazila. Among 20 samples, every 10 samples were collected from tobacco and non-tobacco land at a depth of 0 to 15 cm in Bhuapur, 0 to 15 and 15 to 30 cm in Kalihati Upazila. The soil pH, organic matter (OM), total nitrogen (N), available phosphorus (P), available sulfur (S), available zinc (Zn), exchangeable potassium (K), exchangeable magnesium (Mg) and exchangeable calcium (Ca) were analyzed in the laboratory of Soil Resource Development Institute (SRDI), Tangail. In Kalihati Upazila, tobacco land showed significantly higher content of OM, available N, available P, available Zn, exchangeable K and exchangeable Mg, whereas pH was low in non-tobacco land. Surface soil (0 to 15 cm) and tobacco land showed significantly higher content of S than sub-surface (15 to 30 cm) soil and non-tobacco land. On the other hand, there was no significant variation between tobacco and non-tobacco land on soil properties in Bhuapur Upazila. In both Upazilas, all the nutrients except exchangeable Ca and Mg were lower than optimum in tobacco and non-tobacco land, which was unsuitable for crop cultivation. The cost of production was higher in tobacco land than in non-tobacco land in both Upazilas. About 36% of farmers informed that they were suffering from various diseases due to tobacco cultivation and curing. Tobacco cultivation in these areas degrades soil health and the agricultural ecosystem and releases nicotine into the environment, hampering food safety and human health. The study indicated that tobacco cultivation should be replaced by other crops to protect soil quality and human health.Int. J. Agril. Res. Innov. Tech. 12(2): 27-35, December 2022